Especially the Development of Myocarditis in Hypothyroidism in Postnatal Ontogenesis - Mirzamukhamedov O.Kh.1, Mirsharopov U.M.2, Sodikova Z.Sh.3, Akhmedova S.M.4, Khatamov A.I.5, Mirzabe (Indian Journal of Forensic Medicine & Toxicology, 2020)
The morphological changes in the myocardium of the offspring were studied when the mother hadhypothyroidism in the rat to the female mother during the feeding of the rats.The aim of our work was to identify structural and morphological changes in the walls of the heart of babyrats born to mothers in a state of hypothyroidism and the use of the antioxidant Mexidol.The material for the experiment, served microscopic myocardial preparations of 50 rats of different periodsof early postnatal ontogenesis.Results: The morphological structure of the myocardium of the heart of baby rats born to mothers, dystrophicchanges were observed in a state of hypothyroidism. The observed changes reached a maximum by the 14thday of studies, manifested by perivascular and interstitial lymphohistiocytic infiltrate. Changes should alsooccur in the ultrastructure of the heart, which leads to changes in myofibrils, damage to the mitochondria,which affect the microvessels with a violation of the components of the vascular walls, which are developingintercellular edema